Reuse of industrial wastewater for agriculture area - Abhishek Shehra (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2021)
Now a days we see that a large amount of water has been wasted either in sewage or soil. it suffers from shortage of water supply for irrigation uses. On the other hand, the production system in the Rajasthan region is characterized by many agricultural food industries, the activity of which produces large amounts of wastewater. It is usually discharged into torrents or rivers. To manage this wastewater and also to fulfil the water demand in agriculture area thereby reduce the load on natural water stream, this wastewater should be used for various purposes including agriculture after with or without conventional or advanced treatment. In this project we took two sample of water then we conduct the test. Then analysis the result with irrigation till now we conduct (pH Test, Electrical Conductivity Test, Hardness Test, Alkalinity Test) and all results are good according to the I.S code & I got success to find a new water sources for agricultural purpose. Purpose of the manuscript  • The objective of this manuscript is to analyse the water quality of agro industry wastewater. • The most Common reasons for establishing a reuse program is to identify new water source. Subject: Environmental Pollution.